Transformasi Digital dalam Pendidikan: Pelatihan Pembelajaran Berbasis Canva bagi Guru SDN 65/II Sungai Bangsat: Digital Transformation in Education: Canva-Based Learning Training for Teachers of SDN 65/II Sungai Bangsat - Pajrini, Ani; Riani, Novi; Pertiwi, Linda Ayu; Putri, Aura Nabila (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The digital transformation in education is essential for enhancing learning quality, particularly at the elementary school level. This community engagement program aims to enhance teachers' digital skills through Canva-based learning training for Teachers at SDN 65/II Sungai Bangsat, conducted on January 31–February 1, 2025. The Participatory Action Research (PAR) method was implemented, involving 18 teachers and one school principal as active participants. The training results indicate that 80% of participants were able to create digital teaching materials independently, and 90% agreed that Canva helped enhance learning engagement. Challenges included limited internet access and varying levels of digital proficiency among teachers. Thus, follow-up mentoring, technological infrastructure improvements, and periodic evaluations are necessary to ensure the sustainable use of Canva in teaching. This program enhances teachers' digital literacy and serves as a training model applicable to other elementary schools, particularly in areas with limited technological resources.